Trial Watch: Immunostimulatory monoclonal antibodies for oncological indications - Cabo, Mariona; Offringa, Rienk (OncoImmunology, 2017)
The goal of cancer immunotherapy is to establish new or boost pre-existing anticancer immune responses that eradicate malignant cells while generating immunological memory to prevent disease relapse. Over the past few years, immunomodulatory monoclonal antibodies (mAbs) that block co-inhibitory receptors on immune effectors cells - such as cytotoxic T lymphocyte-associated protein 4 (CTLA4), programmed cell death 1 (PDCD1, best known as PD-1) - or their ligands - such as CD274 (best known as PD-L1) - have proven very successful in this sense. As a consequence, many of such immune checkpoint blockers (ICBs) have already entered the clinical practice for various oncological indications. Considerable attention is currently being attracted by a second group of immunomodulatory mAbs, which are conceived to activate co-stimulatory receptors on immune effector cells. Here, we discuss the mechanisms of action of these immunostimulatory mAbs and summarize recent progress in their preclinical and clinical development.
Gesehen am 05.04.2018